(untitled) (Tempo e Argumento, 2020)
The article deals with how the defense of voluntary termination of pregnancy was a theme embraced by contemporary artists, cartoonists and cartoonists who are attuned to feminist demands, focusing on the series "Dicas do Abortinho", created by cartoonist Fabiane Langona. In the first part of the text, I present briefly three specific works that, with different approaches, discuss taboos, myths and the risks inherent in the practice of clandestine abortion: the autobiographical comic book narrative drawn by cartoonist Cynthia B, published in Piauí magazine , in 2014; the graphic novel produced in 2015 by artist Leah Hayes; and the graphic report, written in 2016 by journalist Joyce Gomes and comic artist Helô D’Angelo, author of the drawings. In the second part, I specifically analyze the character “Abortinho”, highlighting the visual and discursive strategies employed by the cartoonist to treat this theme as a social and political problem, although it has generated significant hostility. between readers and readers. I understand that the reaction to the Abortinho series was less due to the visual impact that the series has on its readers, than to the density that the abortion theme carries, after all the defense of the rights to the body and the liberation of abortion are the biggest challenges. faced by contemporary feminisms. Keywords: Abortion. Comics. Fabiane Langona. Feminism.